Wireless Vein and Artery Identifier for Laparoscopic Instruments - Torres-Ventura, J.; Reyna, M. A.; Rascón, R.; Avitia, R. L.; Bravo-Zanoguera, M. E. (Revista Mexicana de Ingenieria Biomedica, 2017)
This article presents an innovation on a conventional laparoscopic instrument, to which was added the automatic function to identify veins and arteries. It is proposed the use of a reflective-optical sensor with a specific work wavelength acting on blood vessels. The discrimination success between veins and arteries is achieved based on the range of difference between the light emitted and the light reflected. At the tip of a laparoscopic instrument was fitted a reflective-optical sensor composed of a LED and a light dependent resistor. In the upper part of the instrument an electronic control, processing and radio frequency transmitter module was fitted, which warns the surgeon and his assistants if the detected blood vessel is a vein or artery. The instrument was tested in vitro using whole human blood samples and in vivo on canine model blood vessels. With the innovation a low-cost support tool is achieved that could aid the surgeon when working on minimally invasive environments.